2008
DOI: 10.1021/om700700q
|View full text |Cite
|
Sign up to set email alerts
|

First Copper(I) Ferrocenyltetraphosphine Complexes: Possible Involvement in Sonogashira Cross-Coupling Reaction?

Abstract: Preparation and characterization of the first examples of copper(I) ferrocenylpolyphosphine complexes are reported. The molecular structure of complex {P,P′,P′′-[1,1′,2,2′-tetrakis(diphenylphosphino)-4,4′di-tert-butylferrocene]iodocopper(I)} (1) was solved by X-ray diffraction studies, and its fluxional behavior in solution was investigated by VT-31 P NMR; both revealed a net triligated coordination preference of the ferrocenyl tetraphosphine Fc(P) 4t Bu with copper. The tetradentate ligand is an active auxili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 27 publications
(42 reference statements)
0
28
0
Order By: Relevance
“…The exact mechanism of the homogeneous copper co-catalyzed Sonogashira reaction is unknown and is generally supposed to take place through two independent catalytic cycles, as shown in Scheme 21. While the first cycle involving Pd is classical from C C cross-coupling formation, the second cycle generally involving copper (I) iodide is still poorly understood [54].…”
Section: Sonogashira Reactionsmentioning
confidence: 99%
“…The exact mechanism of the homogeneous copper co-catalyzed Sonogashira reaction is unknown and is generally supposed to take place through two independent catalytic cycles, as shown in Scheme 21. While the first cycle involving Pd is classical from C C cross-coupling formation, the second cycle generally involving copper (I) iodide is still poorly understood [54].…”
Section: Sonogashira Reactionsmentioning
confidence: 99%
“…It is widely accepted that the initial generation of a π-alkyne-Cu complex 13 increases the acidity of the terminal alkyne and thus facilitates the base-assisted formation of the copper acetylide 10. However, recent reports suggested further processes involving copper, such as prestabilization of CuI with multidentate polyphosphine ligands and ligand exchange between the participating catalytically active metals [23].…”
Section: Mechanismmentioning
confidence: 99%
“…However, it has been shown that CuI-polyphosphane adducts can be formed and ligands can be transferred from one metal to another, showing that copper-ligand interactions might also be likely in tandem palladium/copper cross-coupling reactions. 146,147 The processes involving the copper-free Sonogashira reaction have been investigated more deeply, even theoretically, 148,149 and the suggested mechanism is depicted in Figure 4.4a. This proposed catalytic cycle is initiated, as usual, by the oxidative addition of the aryl or vinyl halide to the catalytic species [Pd(0)L 2 ].…”
Section: Mechanistic Aspectsmentioning
confidence: 99%